Education and Women's Role in the Musical Field in Ecuador - Remache Coyago, Abel (2025)
This study analyzes the insertion of women in the musical field related to the student and professional space in Ecuador, according to studies and data from educational institutions. Recently, the insertion of women in the education system in Ecuador has been equated with respect to men. Despite this, there is evidence of a latent inequality reflected in aspects such as the number of women in teaching or rectorship positions in higher education. In view of this situation, an analysis and compilation of existing information was carried out with the aim of detecting whether inequality exists in the field of musical education in Ecuador. An exploratory and descriptive research has been carried out, considering the information of the governing entities in Ecuador and of the formally endorsed educational institutions. The results obtained indicate that there is no evidence of equity in the field of musical studies and training, although it does exist at the basic and high school levels. It is in higher education that an enormous gap is observed, with men being the ones who opt for the musical field and occupy, to a large extent, positions as teachers in higher conservatories, musicians and composers in symphony orchestras.